THE IMPACT OF PALM PLANTATION EXPANSION ON THE ECONOMIC, ECOLOGICAL AND SOCIAL DIMENSIONS OF SUSTAINABLE DEVELOPMENT - Lovanie, Dona Eka (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Lambung Mangkurat, 2023)
Oil palm plantations are accused of hurting forest destruction, especially Kalimantan and Sumatra, Indonesia's largest palm oil producers. It is considered unsustainable, so it is a challenge for the area to always pay attention to the use and preservation of the environment to remain maintained and sustainable. This research is intended to analyze the impact of oil palm plantation expansion in three main dimensions, namely economic in the form of national and regional economic growth; ecological, including plantation expansion on land use and climate change; and social, to evaluate the impact of expansion on society in Indonesia. This research uses a qualitative approach with descriptive analysis data collection methods through trusted sources and a literature review regarding the economic, ecological, and social impacts of oil palm plantation expansion. The research results show that (1) In the economic aspect, the palm oil industry contributes to sustainable development, namely generating foreign exchange, regional development, and successfully creating middle-income farmers. The development of oil palm plantations is also inclusive and attracts the development of other sectors. (2) In the social aspect, the palm oil industry plays a role in rural development, reducing poverty, equalizing economic development, and improving income and development inequality. In contrast, (3) From an ecological perspective, oil palm plantations can produce O2 and increase land biomass to reduce emissions. Greenhouse gases. So, in this case, it can be concluded that expanding oil palm plantations requires balanced regulations to control negative impacts, including sustainable management, ecological monitoring, and fulfilling community rights by seeking collaboration between government, industry, and society in achieving sustainable plantations.